Flavian Epic Interactions. - Manuwald, Gesine (Trends in classics. Supplementary volumes., 2013)
This volume on the three Flavian epic poets (Valerius Flaccus, Statius, Silius Italicus) for the first time critically engages with a unique set-up in Roman literary history: the survival of four epic poems from the same period. The interactions of these poems with each other and their contemporary context are explored by over 20 experts and emerging scholars. Together they offer new perspectives to the still increasing readership of Flavian epic poetry.